DYNAMIC MATHEMATICAL SOFTWARE IN THE CONTEXT OF THE MODERN TEACHER’S WORK: THE RESULTS OF THE PEDAGOGICAL EXPERIMENT - Semenikhina О.В.; Drushlyak М.Г. (Journal of Information Technologies in Education (ITE), 2015)
The article presents the results of pedagogical research about the willingness and the psychological readiness to use dynamic mathematical software (DMS) by working and future math teachers. The experiment was conducted during 2010-2014 at the Sumy Makarenko State Pedagogical University. The results of the research demonstrate the dynamics of the increase in the number of teachers and students who wish to use DMS in their future careers. It was used nonparametric method for dependent samples - the McNemar’s test - to handle the results of the research. The hypothesis, that the study of the Special course of the use of dynamic mathematical software by future math teachers has a positive impact on the willingness and the readiness to use such software in their own professional activities, was confirmed at the significance level of 0.05. Additionally, the results of the experiment on the willingness and the readiness to support the teaching of some subjects (algebra, planimetry, solid geometry and analysis) by dynamic mathematical software, and the willingness to use some dynamic mathematical software (Gran ,Gran1, Gran2d, Gran3d), GeoGebra, Сabri, MathKit, DG, GS) by Ukrainian math teachers were given. Analysis of results revealed that working and future math teachers prefer to work with Gran and GeoGebra, respectively. That is why the further work on the creation of educational materials on the use of GeoGebra is useful